Gamifying Education: Evaluating the Role of 'Corner' Video Game in Improving Conceptual Understanding and Learning Interest - Laswadi; Handican, Rhomiy; Arnawa, I Made; Asmar, Ali (Jurnal Edutech Undiksha, 2024)
The need for innovative approaches in mathematics learning has become increasingly urgent to address the challenges of conceptual understanding and foster sustainable learning interest among students. This study aims to evaluate the effectiveness of the educational video game "Corner" in enhancing students' mathematical conceptual understanding and strengthening their interest in learning mathematics. The research employed a quasi-experimental method with a Non-equivalent (Pre-test and Post-test) Control Group Design. The instruments used included a mathematical conceptual understanding test and a mathematics learning interest questionnaire. Data were analyzed using independent sample t-tests and paired sample t-tests to compare the results between the experimental and control groups. The findings revealed that the use of the educational game "Corner" significantly improved students' mathematical conceptual understanding. Additionally, there was an increase in students' interest in learning mathematics, as indicated by significant differences between the pre-test and post-test results in the experimental group compared to the control group. These findings suggest that game-based educational media is not only effective in helping students grasp mathematical concepts but also motivates them to become more active and enthusiastic in learning mathematics. Therefore, the use of game-based learning media such as "Corner" can be adopted by educators as an effective strategy to improve the quality of mathematics education in schools.